Antenatal care practices among the women with children under five-years of age in an eastern Nepal village: A cross sectional study - Subedi, Laxmi; Sah, Ram Bilakshan; Regmi, Mohan Chandra (Journal of Kathmandu Medical College, 2017)
Background: Antenatal care has proven to be an effective way to reduce maternal mortality and save the life of newborn. Nepal also follows the World Health Organization’s recommendations of initiation of four antenatal care visits that has helped in decreasing the maternal mortality of the country. Still, the country has to do a lot in improving the antenatal care provision. Objective: The objective of this study was to find out the antenatal care practices among the women with children less than five years of age in a district of eastern Nepal. Methods: A descriptive cross-sectional study was conducted among residents of Aurabani village of Sunsari district. Non probability convenient sampling technique was used to collect data from 15th January to 30th January, 2015. Data of 100 women having children less than five years of age were collected and analyzed in descriptive and inferential ways. Results: Women with nuclear family are more likely to have antenatal care visits (73.8%) compared to women with joint family (66.7%). The study showed that attendance of antenatal care visits among the educated women was higher (71.8%) than those illiterate (66.7%). In the study, 84.8% of women of primi-gravida completed antenatal care visit which was significantly higher than women with multi gravida (59.3%) (p <0.05). Further, 83.1% of respondents who completed tetanus toxoid injections had not walked <30 meters distance for health services which was significantly higher than those walking >30 meters distance (52.9%). An almost similar trend was found among pregnant women taking iron tablets and vitamin A. Furthermore, walking distance shows stronger association with women taking albendazole during pregnancy (p <0.001). Conclusion: A large percentage of women completed all four recommended antenatal visits. Women and their husbands who were educated placed high importance on antenatal visits. Gravida of the pregnancy was also related to the antenatal care visit. High number of primi-gravida women completed antenatal care visits than women with multigravida. Use of medicines like iron tablets, albendazole tablets, vitamin A and tetanus toxoid injection was directly related with the walking distance to the health center. Journal of Kathmandu Medical College Vol. 5, No. 3, Issue 17, Jul.-Sep., 2016, page: 89-94